Viscoelastically tunable substrates elucidate the interface-relaxation-dependent adhesion and assembly behaviors of epithelial cells. (July 2021) - Chang, Alice Chinghsuan; Uto, Koichro; Homma, Kenta; Nakanishi, Jun
Abstract: Recent progress in mechanobiology sheds light on the regulation of cellular phenotypes by dissipative property of matrices, i.e., viscosity, fluidity, and stress relaxation, in addition to extensively studied elasticity. However, most researches have focused on bulk mechanics, despite cells in 2D culture can only interact with matrix interface directly. Here, we studied the impact of interfacial viscosity as well as elasticity of substrates on the early stage of adhesion behaviors of epithelial cells through new material design and mechanical characterization. The materials are copolymers of ε -caprolactone and d, l -lactide photocrosslinked by benzophenone. The substrate viscoelasticity changes depending on the polymer molecular weight and irradiation time. The interfacial elasticity and relaxation were determined by atomic force microscopy with modes of nanoindentation and tip-dwelling, respectively. MDCK cells changed morphologically, ranging from loose beaded assembly to more compact spheroids and eventual spread monolayer clusters, in response to the interfacial viscoelasticity change. Such morphological changes were mainly determined by substrate interfacial relaxation, rather than interfacial elasticity. Single-cell tracking identified biphasic motility with the minimum speed at intermediate relaxation time (~350 ms), where cells showed transitional morphologies between epithelial and mesenchymal traits. In that relaxation level, partially deformed cells moved around to coalesce with surrounding cells, eventually assembling into compact cellular aggregates. These results highlight, unlike the conventional hanging-drop technique, an appropriate level of interfacial relaxation is critical for efficient cell aggregate maturation on adhesive viscoelastic matrices. This work not only elucidates that the interfacial relaxation as the essential mechanical parameter for epithelial cell adhesion and migration, but also gives useful tips for creating physiologically relevant drug screening platform. Graphical abstract: Image 1